RETRACTED: Numerical study of hydrodynamics processes fluidized bed - Feoktistov I.I.; Kovalev D.S.; Maltsev A.S.; Mechnik D.A. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001